Morphological and immunohistochemical markers in drowning cases of green turtles on the coast of Espírito Santo, Brazil - Gagliotti, Gabrielle Fernanda Pereira da Silva (2024)
Sea turtles, particularly green turtles (Chelonia mydas), play a crucial role in coastal ecosystems but face different conservation threats, prominently interactions with fisheries.This study aimed to contribute to the diagnosis and understanding of drowning mechanisms in green turtles found along the Espírito Santo coast, employing morphological and immunohistochemical analyses. A total of 37 green turtles (35 juveniles and two adults) were evaluated. Based on the protocol established by Projeto Tamar for determining evidence of fishing interaction considering the animals′ history, external body examination, and necropsy findings the turtles were classified into two groups: Group 1 included 16 individuals with “no evidence” of fishing interaction, and Group 2 included 19 individuals with “strong evidence” of fishing interaction.Histopathological analyses of collected organs (lung, liver, kidney, spleen, and heart) were performed using hematoxylin-eosin staining to detect hemodynamic alterations and Mallory\'s phosphotungstic acid hematoxylin staining to assist in diagnosing cardiac muscle necrosis. Immunohistochemistry was employed to assess tissue preservation and immunoreactivity in lung sections, using antibodies against Cd3 protein, vimentin, and smooth muscle actin clone 1A4. Additionally, immunohistochemistry was utilized to evaluate pathological processes associated with drowning. Antibodies targeting p53 protein, aquaporin 5, and hypoxia-inducible factor alpha (HIF1-α) were used for lung tissues, while aquaporin 5, HIF1-, and myoglobin were applied to renal tissues. Histopathological analysis revealed lesions indicative of drowning stress, such as congestion, hemorrhages, and pulmonary edema. However, immunohistochemistry showed significant limitations, as most tested antibodies failed to yield effective labeling. This could be attributed to antigenic characteristics inherent to the species or to the formalin fixation duration, which may compromise antigenic activity. This study underscores the importance of developing standardized protocols for diagnosing drowning and fishing interactions in sea turtles, enabling the impacts of fishing activities on the conservation of these endangered species to be accurately assessed and mitigated.